2022
DOI: 10.14720/aas.2022.118.2.1867
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic and physiological indicators of soybean inoculated of Bradyrhizobium japonicum single-strain in 7 days before sowing

Abstract: <p class="042abstractstekst">Results of investigation of soybean of the Almaz variety in inoculation with preparations based on nodule bacteria <em>Bradyrhizobium japonicum</em> (Kirchner, 1896), Jordan, 1982 B78, B157, D37, D87 are presented. Different periods of the soybean seeds inoculation were used - on the sowing day (control) and in 7 days before sowing (experimental variants). The differences between control and experimental plants in the formation and functioning of the symbiotic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…In addition, the latter authors demonstrated a strong correlation between nodule dry weight and pod dry weight. Vorobey et al (2022) reported that, on average, the number of nodules formed on a single soybean root after seed inoculation ranged from 14 to 45. Other study demonstrated that the weight of nodules on a single soybean Effect of Soybean Seed Inoculation with Symbiotic Bacteria root ranged from 0.22 to 0.24 g, depending on the experimental soil conditions .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the latter authors demonstrated a strong correlation between nodule dry weight and pod dry weight. Vorobey et al (2022) reported that, on average, the number of nodules formed on a single soybean root after seed inoculation ranged from 14 to 45. Other study demonstrated that the weight of nodules on a single soybean Effect of Soybean Seed Inoculation with Symbiotic Bacteria root ranged from 0.22 to 0.24 g, depending on the experimental soil conditions .…”
Section: Resultsmentioning
confidence: 99%